Detection and feature extraction of CT lung tumor using cad system - Josephin Arockia Dhivya, A; J. Hemalatha, R; R. Thamizhvani, T; Elsa Joseph, Josline; Babu, Bincy; Chandrasekaran, R (International Journal of Engineering and Technology, 2018)
A 64 slice computed tomography is used for treating pulmonary related embolism diseases.Pulmonary embolism is a condition which causes death for all age group people.In a decade analyzing, computed tomography technique is regarded as the minimally painful technique.In this condition basically there are five steps involved in it.The first step involved is segmenting the lung sec-tion.The second step briefly delivers about PE extraction using a mask of high intensity.The third step involves in extracting the features in the image.The fourth step is reducing the features using artificial neural networks.The fifth step involves a multi fea-ture system having k as its neighbor,which is helpful for classifying positive and negative differentiation.There are few other methods to improve the performance.:They use tobogganing algorithm and they use the method of grouping and it attained the sensitivity of 80%Other scoring methods are achieved and performance has been enhanced.It also improves CAD performance.Â Â Â